Impact of physician payment mechanism on emergency department operational performance. Issue 2 (14th March 2018) - Innes, Grant D.; Scheuermeyer, Frank X.; Marsden, Julian; Sing, Chad Kim; Kalla, Dan; Stenstrom, Rob; Law, Michael; Grafstein, Eric
Abstract : CLINICIAN'S CAPSULE : What is known about the topic? Fee-for-service compensation may motivate physicians to see more patients and improve throughput, or drive excessive testing and referral behaviour that undermine emergency performance. What did this study ask? Does fee-for-service payment reduce emergency wait times, length of stay, and left without being seen rates? What did this study find? We observed an unsustained 24% reduction in time to physician, but no change in length of stay or left without being seen rates. Why does this study matter to clinicians? Fee-for-service compensation may have transient motivational effect but is unlikely to generate system-level improvement. ABSTRACT: Objective: Fee-for-service payment may motivate physicians to see more patients and achieve higher productivity. In 2015, emergency physicians at one Vancouver hospital switched to fee-for-service payment, while those at a sister hospital remained on contract, creating a natural experiment where the compensation method changed, but other factors remained constant. Our hypothesis was that fee-for-service payment would increase physician efficiency and reduce patient wait times. Methods: This interrupted time series with concurrent control analysed emergency department (ED) performance during a 42-week period, encompassing the intervention (fee for service). Data were aggregated by week and plotted in a time series fashion. We adjusted for autocorrelation and developed general linear regression models to assess level and trend changes. Our primary outcome was the wait time to physician. Results: Data from 142, 361 ED visits were analysed. Baseline wait times rose at both sites during the pre-intervention phase. Immediately post-intervention, the median wait time increased by 2.4 minutes at the control site and fell by 7.2 minutes at the intervention site (difference=9.6 minutes; 95% confidence interval, 2.9-16.4; p =0.007). The wait time trend (slope) subsequently deteriorated by 0.5 minutes per week at the intervention site relative to the expected counterfactual ( p for the trend difference=0.07). By the end of the study, cross-site differences had not changed significantly from baseline. Conclusion: Fee-for-service payment was associated with a 9.6-minute (24%) reduction in wait time, compatible with an extrinsic motivational effect; however, this was not sustained, and the intervention had no impact on other operational parameters studied. Physician compensation is an important policy issue but may not be a primary determinant of ED operational efficiency. RÉSUMÉ: Objectif: Le mode de paiement à l'acte peut inciter les médecins à voir plus de patients et ainsi à accroître la productivité. En 2015, des urgentologues travaillant dans un hôpital de Vancouver sont passés au mode de paiement à l'acte, tandis que d'autres travaillant dans un hôpital de type et de grosseur comparables ont conservé le mode de paiement contractuel, ce qui a permis de mener une expérience naturelle dans laquelle seuls les modes de rémunération avaient changé, les autres facteurs étant restés égaux par ailleurs. Aussi l'étude visait-elle à vérifier l'hypothèse selon laquelle le paiement à l'acte augmenterait l'efficience des médecins et réduirait le délai d'attente des patients. Méthode: Il s'agit d'une étude de séries temporelles interrompues, comparative avec témoin concomitant, qui visait à analyser la performance au service des urgences (SU) sur une période de 42 semaines, après la mise en œuvre de l'intervention (le paiement à l'acte). Les données ont d'abord été agrégées sur une base hebdomadaire, puis représentées sous forme de graphique tracé en fonction des séries temporelles. Il y a eu un rajustement des données pour tenir compte de l'autocorrélation et nous avons élaboré des modèles généraux de régression linéaire afin d'évaluer les changements de valeur et de tendance. Le principal critère d'évaluation était le délai d'attente des patients avant la consultation médicale. Résultats: Ont été recueillies, puis analysées des données concernant 142 361 consultations au SU. Les délais d'attente ont augmenté au départ dans les deux hôpitaux durant la phase avant l'intervention. Immédiatement après l'intervention, le délai d'attente médian a augmenté de 2, 4 minutes dans le centre témoin et a diminué de 7, 2 minutes dans le centre expérimental (écart=9, 6 minutes; intervalle de confiance à 95 % : 2, 9-16, 4; p =0, 007). Par la suite, le délai d'attente s'est détérioré et tendait (pente) à augmenter de 0, 5 minute par semaine, dans le centre expérimental par rapport à la valeur contre-factuelle prévue (écart de tendance : p =0, 07). À la fin de l'étude, l'écart entre les deux hôpitaux avait peu changé par rapport aux valeurs de départ. Conclusion: Le mode de paiement à l'acte a certes été associé à une réduction du délai d'attente de 9, 6 minutes (24 %), réduction compatible avec un effet de motivation extrinsèque, mais le rythme ne s'est pas maintenu par la suite, si bien que l'intervention n'a eu aucune incidence sur d'autres paramètres fonctionnels étudiés. La rémunération des médecins soulève une question importante de politique, mais elle pourrait bien ne pas constituer un déterminant fondamental de l'efficience opérationnelle au SU.